Failure Factors & Prediction Model of Indonesian Medical Doctor Proficiency & Competency Test (UKMPPD) within COVID-19 Pandemic - Salim, Jonathan; Arnindita, Jannatin Nisa; Tandy, Sutiono; Wibisono, Jacobus Jeno; Wibisono, Maria Georgina (Fakultas Kedokteran Universitas Pelita Harapan, 2022)
Background: Coronavirus Disease 2019 drastically modulate the healthcare world. The pandemic's immense transmission and lethality rate enforce the Indonesian Medical Doctor Proficiency & Competency Test to discard practical measures and rely only on a written exam. These with pandemic social and physical restrictions impede prospective doctors’ learning opportunities leading to easier failure. Henceforth, the present study has high urgency to identify and manage failure factors, especially in the pandemic.Methods: The cross-sectional study examines 75 clinical medical students through purposive analysis with an online questionnaire in August 2021. Data are analyzed with Chi-Square, Mann-Whitney, and binary logistics.Result: Respondents have an average age of 24.15 (1.322) years old, majorly female (82.7%), and pass as first takers (86.7%) with 1.27 (0.949) off-campus tutelage. The significant factors for the test failure are depression and economic status. The study developed a failure prediction model with the area under the curve 0.845, cut-off 366.5, 80.0% sensitivity, and 84.6% specificity.Conclusion: Intrinsic, extrinsic, and academic factors have significant roles in the failure outcome. For this reason, preparation is crucial not only among individuals but also institutions. The study also provides feedback about the importance of mental health and economic status for Indonesian medical students